From contact tracing to COVID-19 pass holder; the tortured journey of the French TousAntiCovid contact tracing app. (May 2022) - Schultz, Émilien; Touzani, Rajae; Mancini, Julien; Ward, Jeremy K.
Abstract: Objectives: Our study aimed to provide an updated overview of the use of the French contact tracing application, TousAntiCovid, and identify evolutions since the beginning of the pandemic. Study design: We conducted a survey study on a representative sample of the French adult population. Methods: Our data were collected by the Obervatoire Régional de la Santé (ORS) using a self-administered online questionnaire. This was completed by a sample of 2, 022 people stratified to match French official census statistics for gender, age, occupation, and area of housing. We conducted statistical analysis using Python (Pandas – Scipy - Statsmodels) with chi-squared and Wilcoxon rank-sum tests to control for statistical significance. Results: A small majority of respondents used TousAntiCovid (55.5%), while 41.0% had never downloaded it. Only one-quarter of the respondents (23.3%) used it for contact tracing with Bluetooth, while a third (32.2%) used it only for storing their health pass. The app's use increased with education level, income, and younger age. A large majority (85%) of non-vaccinated respondents had never downloaded TousAntiCovid. Conclusion: Our results suggest that the role and use of France's official COVID-19 app TousAntiCovid has evolved in line with the government's strategy; while initially focusing on contact tracing, its development has led to the possibility to store test and vaccination documentation. The survey also confirmed previous results pointing to the lasting differences in socio-economic status in terms of adoption of the app. This is problematic because the long-term nature of the pandemic could require the government to keep a range of strategies open, including contact tracing. Public discussion of the current and future roles of the French contact tracing app is therefore needed.